Penerapan Kesehatan dan Keselamatan Kerja dengan Perilaku Pencegahan Penularan Covid 19 pada Petugas Kesehatan: Implementation of Occupational Health and Safety with Covid-19 Transmission Prevention Behavior on Health Officers - Hasan, Muhammad Abdul Fatah; Sarwili, Indri; Gunardi, Saiful (Journal of Public Health Education, 2022)
Introduction: The low awareness of the importance of hospital K3 in Indonesia can be seen from the high number of work accidents and occupational diseases in hospitals. Objective: This research aims to determine the relationship between the implementation of occupational health and safety and the behavior of preventing COVID-19 transmission among health workers. Methods: This type of research is quantitative research. The design used in this research is descriptive correlation carried out using a cross-sectional approach. The population in this study were all 63 nurses in the emergency room at Cibinong Regional Hospital. The sample in this research was 63 respondents with a sampling technique using Total Sampling. The researcher analyzed the data using the chi-square test. Results: Based on the results of statistical tests, it is known that the value P = 0.018 means P <0.05. Conclusion: There is a relationship between the implementation of occupational health and safety and the behavior of preventing the transmission of Covid-19 among health workers.